PELATIHAN PEMBUATAN MINUMAN PROBIOTIK THE KOMBUCHA BAGI GURU PAUD GUGUS CAHAYA JINGGA KABUPATEN BINTAN - Siska Amelia Maldin; Tito Pratama; Dewi Aurora (PUSLITABMAS-Politeknik Pariwisata Batamc, 2023)
Community service is one of the mandatory tasks of lecturers as part of the realization of the Tri Dharma activities of Higher Education. In line with this, Tri Dharma activities are focused on important activities in contributing to improving the quality of life of the community, especially in developing skills that can be used in a wider scope of society. One of the activities carried out was the training of kombucha tea making techniques for PAUD teachers of GUGUS CAHAYA JINGGA at Batam Tourism Polytechnic. This training aims to provide information to teachers of PAUD Cahaya Jingga Cluster regarding the ingredients and process of making kombucha tea, knowing the time needed to produce fermented products, and knowing the morphological and chemical characteristics of kombucha tea. The specific target to be achieved is to make PAUD GUGUS CAHAYA JINGGA teachers skilled in processing kombucha tea products and can develop them in entrepreneurship so as to support financially in the economy.